2004
DOI: 10.1021/bm049727w
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl chloride)-Coated Sol−Gels for Studying the Effects of Nitric Oxide Release on Bacterial Adhesion

Abstract: Nitric oxide (NO) releasing sol-gel materials coated with poly(vinyl chloride) (PVC) films exhibit increased stability at ambient and physiological temperatures. The polymer overcoat, however, reduces the NO fluxes by 5-35% over the initial week of release. The variation in NO fluxes between unmodified and PVC-coated sol-gels is negligible after 7 days. The PVC polymeric layer provides controlled surface chemistry for systematic studies of the effects of NO release on bacterial adhesion. As an example, the adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 25 publications
(71 reference statements)
8
52
0
2
Order By: Relevance
“…For this purpose, a standard monofilament polypropylene mesh was equipped with an NO-releasing coating and challenged by several bacterial strains in vitro as well as in vivo. In vitro evaluation of the biofilms showed that bacterial survival on our NO-releasing meshes was significantly reduced for all strains, which is in line with other in vitro studies evaluating NO-releasing coatings on medical-grade stainless steel [12] or silicone rubber [19], despite the fact that the NO released from our C-based coating was almost six times lower than from N-based coating generally used [13][14][15]28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For this purpose, a standard monofilament polypropylene mesh was equipped with an NO-releasing coating and challenged by several bacterial strains in vitro as well as in vivo. In vitro evaluation of the biofilms showed that bacterial survival on our NO-releasing meshes was significantly reduced for all strains, which is in line with other in vitro studies evaluating NO-releasing coatings on medical-grade stainless steel [12] or silicone rubber [19], despite the fact that the NO released from our C-based coating was almost six times lower than from N-based coating generally used [13][14][15]28].…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, localized high levels of NO in the vicinity of an implant may reduce the risk of both early and late infection as the NO will kill peroperatively introduced bacteria. It has been shown that coatings capable of releasing NO significantly inhibit adhesion and survival of P. aeruginosa on implant surfaces in vitro [12][13][14][15]. A number of studies have evaluated the effects of NO in vivo, as released from nitrogen-based (N-based) polymer coatings, such as N-based diazeniumdiolate coatings.…”
Section: Introductionmentioning
confidence: 99%
“…2). Even so, some NO flux was detectable for up to 7 d. These NO properties and the durability of 40% AHAP3 sol-gel films make them excellent candidates for antibacterial medical coatings [10,11]. A burst of NO will be delivered immediately after implantation during the initial stages of potential bacterial colonization.…”
Section: Nitric Oxide Releasementioning
confidence: 99%
“…Intensive in vitro antibacterial studies have been performed characterizing the efficacy of NO release as a strategy to reduce bacterial adhesion [4,[9][10][11] The adhesion of three common opportunistic pathogens Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis has been shown to decrease in the presence of a low surface flux of NO. An in vitro biomaterial comparison suggests that the bacterialadhesion resistance of medical-grade stainless steel may be dramatically improved with the application of a NO-releasing xerogel layer [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation